HUBUNGAN SELF EFFICACY PERAWAT DENGAN KEMAMPUAN PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI RUANG ICU - Dinda Cantika Rahma (2023)
Self efficacy is a form of belief in designing and carry out actions to achieve the desired goals. Self efficacy is related to one's ability to control thoughts, feelings, attitudes, behaviors or actions. Self efficacy is one of the factors that influence nurses in fulfilling spiritual needs. Spirituality becomes one of the important aspects of human life, where spirituality can be a source of coping for individuals who are stressed or related to the illness they are experiencing. Purpose: This study aims to determine the relationship between self-efficacy of nurses and the ability fulfilling patients spiritual needs in the ICU. Method: The research method uses Cross Sectional with a sampling technique using total sampling with a total sample of 60 nurses in the intensive care unit. Results: The results of univariate analysis showed that 60 respondents answered Nurse's self-efficacy is at a high level (63.3%) with the ability to fulfill spiritual needs at a high level (53.3%). Bivariate analysis used Chi Square test with the results showed p value of 0.023 <0.05 and OR of 4.1. This shows that there is a significant relationship between nurses self efficacy with the ability fulfilling patients spiritual needs in the icu room.